SINTESIS DAN KARAKTERISASI SENYAWA ION PERAK KLORIDA (AgCl) MELALUI REAKSI PRESIPITASI DAN ANALISIS SIFAT KELARUTAN - Iis Siti Jahro; Meyla Isnaini Sitorus; Mery Juana; Muhammad Ade Ikhsani; Sartika Mahdalena Pasaribu (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study is based on the importance of understanding precipitation reactions, solubility, and the characteristics of ionic compounds through laboratory experiments. The aim of this research is to synthesize silver chloride (AgCl) via a precipitation reaction, observe the physical characteristics of the resulting precipitate, and examine its solubility in water. The method applied was an experimental approach by mixing 0.01 M AgNO? and NaCl solutions, followed by filtration, drying, and weighing to obtain the experimental mass as well as to calculate the theoretical mass and percentage error. The results indicated the formation of a white AgCl precipitate with a mass of 0.26 grams. The precipitate showed a slight purplish discoloration after exposure to light, indicating its photosensitive nature. The solubility test revealed that AgCl is insoluble in water. The percentage error was found to be 27.8%, which may be attributed to incomplete drying, the presence of impurities, and inaccuracies during filtration and weighing processes. Future studies are recommended to ensure complete drying until constant mass is achieved, reduce contamination, and improve precision in each experimental step to obtain more accurate results.   Keywords: Precipitation, Silver Chloride (AgCl), Solubility, Gravimetry, Photosensitive   Abstrak: Penelitian ini dilatarbelakangi oleh pentingnya pemahaman konsep reaksi presipitasi, kelarutan, dan karakteristik senyawa ionik melalui kegiatan eksperimen laboratorium. Tujuan penelitian ini adalah untuk mensintesis senyawa perak klorida (AgCl) melalui reaksi presipitasi, mengkarakterisasi sifat fisik yang terbentuk, serta menganalisis sifat kelarutannya dalam air. Metode yang digunakan adalah metode eksperimen dengan mencampurkan larutan AgNO? dan NaCl masing-masing 0,01 M, dilanjutkan dengan proses filtrasi, pengeringan, dan penimbangan untuk menentukan massa hasil serta menghitung massa teoritis dan persen kesalahan. Hasil penelitian menunjukkan terbentuknya endapan putih AgCl dengan massa sebesar 0,26 gram yang kemudian mengalami perubahan warna menjadi keunguan akibat pengaruh cahaya (sifat fotosensitif). Uji kelarutan menunjukkan bahwa AgCl tidak larut dalam air. Persen kesalahan yang diperoleh sebesar 27,8% yang disebabkan oleh faktor pengeringan yang belum optimal, adanya pengotor, serta kesalahan dalam proses penyaringan dan penimbangan. Disarankan bagi peneliti selanjutnya untuk meningkatkan ketelitian dalam proses pengeringan hingga mencapai massa konstan, meminimalkan kontaminasi, serta menggunakan teknik pemurnian yang lebih baik agar diperoleh hasil yang lebih akurat.   Kata kunci: Presipitasi, Perak Klorida (AgCl), Kelarutan, Gravimetri, Fotosensitif